Uncertainty propagation in the serviceability assessment of footbridges. Issue 1 (2nd January 2020) - Tubino, Federica; Pagnini, Luisa; Piccardo, Giuseppe
Abstract: This paper discusses the serviceability assessment of footbridges considering the uncertainties in definition of their structural and loading parameters. Application of the Taylor Series Expansion method to the closed-form expression of the dynamic response based on the Equivalent Spectral Model allows to obtain analytical solutions for the quantification of uncertainty propagation and to identify the parameters whose uncertainties may cause significant scatter of the results. The proposed analytical solutions are verified by Monte Carlo simulations, in the two classic scenarios of resonance and non-resonance conditions between step frequency and the bridge natural frequency. The approach provides the possibility of going beyond conventional verifications of footbridge vibration level, based on nominal values of load and structural properties. In this framework, serviceability assessment is proposed from a probabilistic point of view, associating a probability of occurrence to each comfort level.